2017
DOI: 10.1103/physrevmaterials.1.064409
|View full text |Cite
|
Sign up to set email alerts
|

Codoping ofSb2Te3thin films with V and Cr

Abstract: Magnetically doped topological insulators (TIs) are key to realizing the quantum anomalous Hall (QAH) effect, with the prospect of enabling dissipationless electronic devices in the future. Doping of the well-established three-dimensional TIs of the (Bi,Sb)2(Se,Te)3 family with the transition metals Cr and V is now an established approach for observing the QAH state at very low temperatures. While the magnetic transition temperatures of these materials is on the order of 10's of K, full quantization of the QAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…The observed Sb 5p magnetic moment at the non-magnetic element is most likely induced by the V magnetic dopant. This result is in good agreement with the previous XMCD studies for Cr-or V-doped compounds [29,33,35,36,38]. More importantly, very small but clear XMCD signals are observed at the Te M 4,5 absorption edges.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The observed Sb 5p magnetic moment at the non-magnetic element is most likely induced by the V magnetic dopant. This result is in good agreement with the previous XMCD studies for Cr-or V-doped compounds [29,33,35,36,38]. More importantly, very small but clear XMCD signals are observed at the Te M 4,5 absorption edges.…”
Section: Resultssupporting
confidence: 92%
“…The microscopic origin of the ferromagnetism and the QAH state has been extensively investigated by theoretical and experimental approaches [26][27][28][29][30][31][32][33][34][35][36][37][38]. Element-specific x-ray absorption spectroscopy (XAS) and x-ray magnetic circular dichroism (XMCD) experiments revealed that the long-range ferromagnetic order in the magnetic TIs is caused by a magnetic coupling between p-d electrons of the host and magnetic dopants because the clear XMCD signals were observed not only at V (Cr) sites but also at Sb sites [29,33,35,36,38]. In addition, first principles calculations, scanning tunneling microscopy/spectroscopy (STM/STS) and resonant photoemission spectroscopy identified the impurity states of vanadium dopants at or near the Dirac node [26,30,32,36].…”
Section: Introductionmentioning
confidence: 99%
“…The Cr state for the covalent compound Cr 2 Te 3 (54% d 3 and 46% d 4 character in the wave function) resembles that of (V,Cr) x Sb 2− x Te 3 (ref. 26 ), but strongly differs from that of Cr x Sb 2− x Te 3 (ref. 17 ) and Cr x Bi 2− x Se 3 (refs 15,27 ).…”
Section: Resultsmentioning
confidence: 95%
“…In an attempt to increase the useful QAHE temperature range, a number of more unconventional doping approaches have been successfully explored, such as co‐doping, modulation doping to separate the dopant from the charge‐carrying surface state layer, and doping with higher magnetic moment rare earth ions, to name a few. Note that co‐doping with different transition metals can also lead to undesired phase separations in this materials class, while modulation doping with Cr promises greater inherent benefits owing to the nature of the doping mechanism, which have, for example, led to the first successful observation of the axion insulator state . Modulation doping of heterostructures, that is, non‐uniform doping along the growth direction, is a well‐known technique for achieving ultrahigh electron mobilities in III–V semiconductors .…”
Section: Introductionmentioning
confidence: 99%